The genus strychnos in colombia (1946)
Although the genus Strychnos is very well represented in Colombia, especially on the eastern lowlands drained by the tributaries of the Amazon, until recently, exceedingly few specimens of this genus from Colombia were available in the major herbaria of Europe and of the U. S. A. There appears to be no published record of the species that occur in Colombia.